Analisis Kadar Astaxanthin Ekstrak Cangkang Udang Vannamei (Litopenaeus vannamei) Asal Kecamatan Malangke Barat Dengan Metode Spektrofotometri UV-Vis - Afifah, Aulia Nur; Widiastuti, Harti; Muflihunnah, Andi (PHARMACY UMI JOURNAL SYSTEM, 2024)
Shrimp waste consisting of heads, shells, legs and tails contains several components such as protein, chitin, enzymes, minerals, carotenoids, and others. One type of carotenoid found in shrimp waste is astaxanthin. Astaxanthin is a carotenoid pigment with higher antioxidant activity compared to other β-carotene and vitamin E derivatives. The purpose of this study was to determine the levels of astaxanthin in the shells of vannamei shrimp (Litopenaeus vannamei) from West Malangke District. The astaxanthin compound contained in vannamei shrimp shells was extracted using the UAE method and liquid-liquid extraction. The percentage value of the reduction is 0.486%. Qualitative analysis used thin layer chromatography (TLC) and quantitative analysis using UV-Vis spectrophotometry. TLC analysis on the sample obtained an Rf value of 0.254. Analysis by UV-Vis spectrophotometry at a maximum wavelength of 203 nm obtained y = 0.1513x – 0.0819, correlation coefficient (r) = 0.9947, Vx0 = 4.64%, and the average level of astaxanthin = 73.2 %.